Auditors' reports of Bangladesh Rural Advancement Committee for the year ended December 31, 1981 - BRAC (© BRAC, 2016)
This Financial Statement prepared by Howladar Yunus & Co. Chartered Accountants, 67 Dilkusha C/A, Dacca, Bangladesh